GENOTYPE -786CC OF THE ENDOTHELIAL NITRIC OXIDE SYNTHASE GENE NOS3 AS A FACTOR OF ADVERSE CORONARY HEART DISEASE COURSE AND INCREASED ON-TREATMENT PLATELET AGGREGATION - E. F. Muslimova; T. Yu. Rebrova; S. A. Afanasiev; T. N. Sergienko; A. N. Repin (Российский кардиологический журнал)
Aim. To assess the associations of polymorphism T-786C gene NOS3 with the severity of clinical course of coronary heart disease (CHD) and platelet aggregatability in the selection of patients receiving clopidogrel and acetylsalicylic acid (ASA) compounds after selective coronary intervention.Material and methods. In the study, 203 CHD males included, taking ASA and clopidogrel as double antiplatelet therapy for coronary intervention. The test performed, of induced platelet aggregation with adenosine diphosphate (ADP) (2,5 mcM and 5,0 mcM) and epinephrine (0,2 mcM). Genotyping was done with the allele specific polymerase chain reaction (“SNP-express”, SPF Litekh, Russia). Statistics was done with Mann-Whitney test, Kruskal-Wallis test and Pearson chisquare or bi-test by Fisher. Differences were taken as significant at p<0,05.Results. In the studied group, genotypes -786TT, -786TC, -786CC were found with the prevalences 72 (35,4%), 99 (48,8%), 32 (15,8%), respectively. For the carriers of -786CC there was found highest grade of platelet aggregation with ADP 2,5 mcM (p=0,047) and with epinephrine (p=0,008). Carriers of -786TC had the highest left ventricle ejection fraction (p=0,035).Conclusion. In the selection of CHD males taking ASA and clopidogrel, carriage of -786CC polymorphism T-786C gene NOS3 was related to higher platelet aggregation in response to ADP and epinephrine. For these patients, the carriage of genotype -786CC gene NOS3 might be a predictor of thrombotic complications after coronary stenting and more adverse outcome of CHD.